An Analysis of the Coherence of Emotional Discourse of Parting (Hijrān) in Amir Moezi’s “Thou Cameleer! Take not Shelter...” - Aslan Ostovari (مطالعات زبانی و بلاغی)
The study of literary discourse from Semio-semantic point of view has opened a new horizon for understanding and analyzing the complexities of the language of lyrical poem and its fundamental concepts. One of the most important achievements of Semio-semantics is to acknowledge that literary speech is no longer considered as bound to words and sentences and that most of the literary processes go beyond the boundary of sentence into a larger totality called discourse. Therefore, even for an accurate and thorough understanding of the words like ‘love’ and ‘parting,’ which are among the fundamental concepts of Persian lyrical poem, we need to study these words and other related terms in association with relevant discourse totality. Emotional discourse is considered as one of the main domains of expressing feeling in poetry. Since the formation of emotional discourse in every poem begins with diction, this analytical – descriptive research initially investigates the mechanism of the production and perception of meaning, based on the lexical network and its emotional processes in poetry. In doing so, to show the emotional discourse in poetry, this article focuses on the lyrical poem “Thou Cameleer! Take not Shelter...” (Ey sārebān manzel makon …) by Amir Moezi to deal with the meaning of parting (Hijrān) in association with the emotional elements of discourse such as body proper, emotional scenery, discourse disconnection and connectivity. The results of the analysis shows that the fundamental meaning of parting in this poem becomes the core concept, overshadowing all the elements of emotional discourse such as body proper, emotional scenery, discourse disconnection and connectivity, perspective as well as the role of affective verbs, rhythm, and manifestations to reinforce discourse coherence. Also, by considering the relationship between fundamental concepts and lexical network and the elements involved in the emotional process, it is possible to methodically analyze and evaluate emotions in lyrical poetry.